EMU and Ireland's sterling trade - Bannon, Seamus (Statistical and Social Inquiry Society of Ireland, 1996)
Trade with the UK is one of the oldest Irish economic policy issues. It remains highly topical today. When Ireland, on joining the EMS in 1979, broke the currency link with Sterling there were fears of negative implications for our trade with the UK. The dilemma was that should Sterling depreciate against the EMS currencies, a significant strain would be placed on the competitiveness of Irish firms exporting to the UK or competing against UK firms in the domestic and third country markets. Irish industry could therefore find itself in a position akin to standing with one foot on each of two wagons which could move apart at any time. Against that the EMS currencies, and in particular the Deutschmark, offered the prospect of lower inflation for Irish enterprise in the longer-run.
Read before the Society, 28 March 1996
Keywords: Trade dependency; European Monetary Union; 314.15